Potential prognostic markers for predicting onset of dengue hemorrhagic fever. (September 2015) - Banerjee, Shefali; Hann Chu, Justin Jang
Dengue is fast evolving as a global infectious disease with more than 390 million infections reported annually. Despite the considerable amount of research, there are no effective vaccines for dengue and the clinical management of the disease solely relies on the effective medical care and supportive treatment of the patients. Rapid diagnosis and early prediction of the severity of the disease will not only aid the clinical management of the disease but also enable efficient utilization of the medical resources in the resource-poor dengue endemic regions. In this review, we have focused on certain diagnostic and prognostic biomarkers for dengue infection which could have a predictive potential for disease severity in the clinical scenario.